Problem-Based Learning with Pop-Up Books to Boost Mathematical Critical Thinking in 6th Grade Geometry: Systematic Literature Review - Amalia, Siti; Supriadi, Supriadi; Arisetyawan, Andika (Papanda Publisher, 2025)
Geometry presents significant challenges for sixth-grade students due to its abstract nature, while Problem-Based Learning (PBL) implementation often lacks concrete media aligning with students' cognitive development stages. This systematic literature review synthesized empirical evidence on integrating PBL with pop-up book media to enhance mathematical critical thinking skills in sixth-grade geometry education. Following PRISMA 2020 guidelines, five databases (Scopus, ERIC, Garuda, DOAJ, SINTA) were systematically searched for studies published 2018-2024. After rigorous screening, 50 high-quality studies employing experimental, quasi-experimental, development, and meta-analytic designs were included for thematic synthesis. Experimental studies demonstrated large positive effects (mean d=0.87, range: 0.52-1.34) of PBL with pop-up books on critical thinking outcomes compared to traditional instruction. Meta-analyses encompassing over 32,000 students confirmed PBL's superiority (effect sizes d=0.64-1.18). Students showed substantial improvements in analysis, evaluation, spatial reasoning, and problem-solving abilities. Pop-up books' three-dimensional representations enhanced engagement, motivation, and conceptual understanding by making abstract geometric concepts tangible. PBL integrated with pop-up books effectively enhances mathematical critical thinking in geometry when supported by adequate teacher training, well-designed materials, and sufficient implementation time. This review provides comprehensive evidence and practical design principles for educators and curriculum developers implementing this innovative, constructivist-based learning strategy.